Observation of Alfvén eigenmodes driven by fast electrons during lower hybrid wave heating in EAST plasmas. (17th July 2018) - Hu, Wenhui; Li, Jiangang; Xiao, Bingjia; Heidbrink, William W.; Shi, Tonghui; Hu, Youjun; Chen, Jiale; Spong, Donald A.; Liu, Haiqing; Wang, Shouxin; Lin, Shiyao; Li, Yongliang; et al.
Abstract: Toroidal Alfvén eigenmodes (TAE) and ellipticity induced Alfvén eigenmodes (EAE) driven by fast electrons are observed for the first time in steady-state EAST plasmas heated by lower hybrid wave (LHW). For the analyzed discharge four modes appear after the injection of LHW. Comparing experimental observations with simulation, high frequency modes are located near and low frequency mode is near . The two positions are very close to where most of the heating power is deposited and population inversion occurs. Analysis of resonance condition between particles and waves indicates that barely-passing, deeply trapped and barely-trapped electrons can drive the mode.